2020
DOI: 10.17680/erciyesiletisim.654569
|View full text |Cite
|
Sign up to set email alerts
|

Akıllı Cep Telefonu Bağımlılığı: Kişilik Özellikleri ve Kullanım Örüntülerinin Etkinliği Üzerine Bir İnceleme

Abstract: Nowadays smart mobile phones in the world; important information and communication technologies. Previously, only mobile phones capable of sending calls and text/ picture messages; it now provides many functions including email and Internet access, shortrange wireless communications, gaming and entertainment, listening to music, business, social networking, TV viewing, photography, video capture or driving directions, and using GPS. As such, mobile phones have become one of the most widely used technologies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
1
7
0
1
Order By: Relevance
“…In the study, it was revealed that high school students sometimes display their internet addictions and social media usage disorders and that they are indecisive in smartphone addictions. This result shows similarity with the results of related studies based on participants (Bal & Balcı, 2020;Filiz, Erol, Dönmez, & Kurt, 2014) In the study, it was seen that students' internet addictions, social media usage disorders, and smartphone addictions are similar in relation to gender. This result shows parallelism with the results of several studies which revealed that there is no difference according to gender (Anlayışı & Serin, 2019;Caz & Bardakçı, 2019;Aktan, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…In the study, it was revealed that high school students sometimes display their internet addictions and social media usage disorders and that they are indecisive in smartphone addictions. This result shows similarity with the results of related studies based on participants (Bal & Balcı, 2020;Filiz, Erol, Dönmez, & Kurt, 2014) In the study, it was seen that students' internet addictions, social media usage disorders, and smartphone addictions are similar in relation to gender. This result shows parallelism with the results of several studies which revealed that there is no difference according to gender (Anlayışı & Serin, 2019;Caz & Bardakçı, 2019;Aktan, 2018).…”
Section: Discussionsupporting
confidence: 87%
“…When the literature is reviewed, it is seen that there are studies focused on the relationship between personality traits and internet / smartphone addiction that causes phubbing, and these addictive behaviors are related to personality traits (Aktaş ve Yılmaz, 2017;Bal ve Balcı, 2020;Işık ve Kaptangil, 2018;Karaaziz ve Keskindağ, 2015;Karahancı, 2018;Kayiş et al, 2016;Kuss et al, 2013;Servidio, 2014;Zhou et al, 2016). Considering the research findings, personality traits have an effect on phubbing tendency.…”
Section: Discussionmentioning
confidence: 94%
“…(Kayiş et al, 2016;Kuss et al, 2013;Servidio, 2014;Zhou et al, 2016). In addition, it is seen that the attitude of using smart phones, which is the main dynamic of phubbing, is related to personality traits (Aktaş & Yılmaz, 2017;Bal & Balcı, 2020;Işık & Kaptangil, 2018;Karaaziz & Keskindağ, 2015;Karahancı, 2018). The emergence of phubbing behavior is directly related to the existence of smartphones and internet applications (T'ng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Smartphones have an important place in the lives of young people for various reasons (Özkoçak, 2016;Bal and Balcı, 2020). Exact data for smartphone usage in Turkey not available, but 2016 Turkish Statistical Institute report stated that 96.8% of the Turkish population possessed a smartphone (Türkiye İstatistik Kurumu, 2020).…”
mentioning
confidence: 99%
“…Despite the many conveniences that smartphones offer, problematic usage may lead to health problems (Darcin, Köse, Noyan et al, 2016). The negative impact of smartphones on young people in particular has been discussed in psychological, sociological, cultural, economic, and pedagogical aspects (Bal et al, 2020). However, to the best of our knowledge, no study has examined the relationship between smartphone addiction and OB.…”
mentioning
confidence: 99%